2010
DOI: 10.1002/pmic.200900557
|View full text |Cite
|
Sign up to set email alerts
|

Immunoproteomic analyses of outer membrane proteins ofMannheimia haemolyticaand identification of potential vaccine candidates

Abstract: Immunoproteomic analyses were used to characterize the outer membrane proteome of Mannheimia haemolytica, formerly Pasteurella haemolytica, serotype 1, and determine potential vaccine candidate proteins. 2-DE of M. haemolytica outer membranes was followed by immunoblot analyses using naïve and convalescent bovine sera. Proteins were identified using MALDI-TOF and LC-MS/MS. Spectral data was used to mine M. haemolytica protein database and 132 immunoreactive proteins were identified. Bioinformatic analysis usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 83 publications
0
29
0
1
Order By: Relevance
“…Mannheimia haemolytica serotype S1, strain 89010807N, originally isolated from a case of calf pneumonia, was used for this study (20). Growth conditions of the bacterium have been described previously (4).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mannheimia haemolytica serotype S1, strain 89010807N, originally isolated from a case of calf pneumonia, was used for this study (20). Growth conditions of the bacterium have been described previously (4).…”
Section: Methodsmentioning
confidence: 99%
“…An immunoproteomic study of M. haemolytica OMPs conducted in our laboratory identified 57 OMPs that may have the potential to be developed into vaccines (4). The immunogenicity of recombinant forms of several M. haemolytica OMPs, including PlpE, OmpA, PlpF, OmpP2, serotype 1-specific antigen (SSA-1), and OmpD15, has been studied (5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Several studies have demonstrated the importance of M. haemolytica OMPs as surface antigens and their potential as vaccine components (3,14,56,57,61). Antibodies against the immunogenic and surface-exposed lipoprotein PlpE contribute toward host defense (60), and the addition of recombinant PlpE to commercial vaccines significantly enhances protection against experimental challenge (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…SSA-1 colony and 2D gel immunoblots with bovine convalescent-phase anti-M. haemolytica sera previously demonstrated high antibody responses to the native protein (4,30). Southern blotting demonstrated genomic fragments homologous to ssa1 in numerous M. haemolytica serotypes, and sequence homology between the ssa1 genes from serotypes 1 and 2 is Ͼ99% (19,21).…”
Section: Discussionmentioning
confidence: 99%
“…We therefore undertook the process of identifying other OMPs that may be important immunogens. Through immunoproteomic analyses using two-dimensional (2D) gel electrophoresis and Western blots of M. haemolytica outer membrane preparations probed with convalescent-phase cattle sera, we identified several additional OMPs of interest for further study (4). We cloned and expressed the genes for five of these proteins, namely PlpF, serotype 1-specific antigen (SSA-1), OmpA, OmpP2, and OmpD15, and then purified the proteins.…”
mentioning
confidence: 99%